2019
DOI: 10.18502/ijph.v48i1.777
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Human Papillomavirus Infection and Smoking, Age, Gender in Lung Cancer Patients: A Meta-Analysis

Abstract: Background: The aim of our study was to identify the association between Human papillomavirus (HPV) positive rate and smoking in lung cancer (LC) patients. Meanwhile, to analyze differences among gender, age differences on HPV infection rate in LC patients. Methods: We performed a systematic literature search through PubMed, Wan Fang, China National Knowledge Infrastructure (CNKI), MEDLINE, EMBASE (OVID), and Web of Science databases from 1991-2017, and we searched these keywords such as "lung cancer", "HPV", … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…However, miR-96 showed significantly higher diagnostic potential (AUC = 0.9735) than miR-1246 (AUC = 0.6761). Wu et al (100) focused on human papillomavirus (HPV) infection, which seems to be a dangerous risk factor in cancer patients (136)(137)(138). They found that miR-183, miR-210, and miR-182 were significantly higher, and miR-144 was markedly lower in HPV-DNA-positive NSCLC than in HPV-DNA-negative NSCLC patients.…”
Section: Circulating Mirnas As Diagnostic Biomarkers For Nsclcmentioning
confidence: 99%
“…However, miR-96 showed significantly higher diagnostic potential (AUC = 0.9735) than miR-1246 (AUC = 0.6761). Wu et al (100) focused on human papillomavirus (HPV) infection, which seems to be a dangerous risk factor in cancer patients (136)(137)(138). They found that miR-183, miR-210, and miR-182 were significantly higher, and miR-144 was markedly lower in HPV-DNA-positive NSCLC than in HPV-DNA-negative NSCLC patients.…”
Section: Circulating Mirnas As Diagnostic Biomarkers For Nsclcmentioning
confidence: 99%
“…Additionally, a Chinese a study developed to identify the association between HPV positive rate and smoking in lung cancer (LC) patients observed that HPV infections are associated with smoking in LC patients and the association may relate to different regions [23]. Lung cancer study of Brazilian patients, the presence of HPV was detected by PCR followed by genotyping, found HPV in 33 of the 63 samples, and HPV types 16 and 18 were detected with frequencies of 81% (27/33) and 19% (6/33), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Cellular Microbiology successful even with the above features when applied together [44]. In the literature, HPV prevalence and activity still are controversial [3,45]. The difference between HPV detection in lung samples may vary due to increased sensitivity of qPCR compared to the conventional PCR screening, DNA extraction method, and geographic location [43,[46][47][48][49].…”
mentioning
confidence: 99%